Characterization of Critical Hemodynamics Contributing to Aneurysmal Remodeling at the Basilar Terminus in a Rabbit Model - Metaxa, Eleni (2010)
BACKGROUND AND PURPOSE: Hemodynamic insult by bilateral common carotid artery (CCA) ligation has been shown to induce aneurysmal remodeling at the basilar terminus in a rabbit model. To characterize critical hemodynamics that initiate this remodeling, we applied a novel hemodynamics-histology co-mapping technique. METHODS: Eight rabbits received bilateral CCA ligation to increase basilar artery flow. Three underwent sham operations. Hemodynamic insult at the basilar terminus was assessed by computational fluid dynamics. Bifurcation tissue was harvested on day 5; histology was co-mapped with initial postligation hemodynamic fields of wall shear stress (WSS) and WSS gradient (WSSG). RESULTS: All bifurcations showed internal elastic lamina (IEL) loss in periapical regions exposed to accelerating flow with high WSS and positive WSSG. IEL damage happened 100% of the time at locations where WSS>122 Pa and WSSG>530 Pa/mm. The degree of destructive remodeling accounting for IEL loss, medial thinning, and luminal bulging correlated with the magnitude of the hemodynamic insult. CONCLUSIONS: Aneurysmal remodeling initiates when local hemodynamic forces exceed specific limits at the rabbit basilar terminus. A combination of high WSS and positive WSSG represents “dangerous” hemodynamics likely to induce aneurysmal remodeling.